Passive Voice in Short Stories: Analytical Study (Journal of the College of Basic Education, 2023)
A short story is a work of fiction. A prose narrative of shorter length thanthe novel, and it usually concentrates on a single theme. Many writers preferwriting short stories when they want to present a single significant episode orscene involving a limited number of characters.Writers differ in their style, but they agree on certain basic elements inwriting the short story. Readers also differ in their preference, some might prefercrime short stories, others like fantasy ones, while many are obsessed byromance or mystery short stories.The way in which the writers present their short stories is restricted toeach writer’s point of view and the angle from which he wants to show hisopinion and makes it apprehensive for his readers. So different parts of speechare involved in writing short stories, and different structures are used, but thefocus of this paper is on the use of passive voice in short stories. Do writersprefer or prefer not to use the passive voice in their writings, and if they doprefer using it, will this affect the phrasing of the short story in a way that ties upthe process of comprehension in the mind of the reader? This paper tries toanswer this question, depending on the analysis of four short stories, chosenfrom different types for different writers.